Animal health inputs, endogenous risk, general infrastructure, technology adoption and industrialized animal agriculture. (February 2019) - Hennessy, David A.; Zhang, Jing; Bai, Na
Highlights: A microeconomic model of animal feeding and genetic selection in CAFOs is developed. Correlations between feeding intensity, genetic selection and biosecurity are explained. Feed additives promote feed intensity while additive regulation reduce intensity. Confined animal feeding is more sustainable in terms of protein output per feed calorie input. Improvements in economy-wide infrastructure that reduce risk of herd loss will promote animal sector industrialization. Abstract: This paper develops a microeconomic model of concentrated animal feeding operations that admits roles for all of animal health inputs, genetic profile choices and the pertaining economic infrastructure. The basic model emphasizes how time on feed, feed density and biosecurity choices interact, as well as how these choices respond to (i) input prices, and (ii) attributes regarding animal productivity parameters that might be influenced by policy choices such as animal welfare strictures and restraints on use of medication. We show that ostensibly substituting inputs in protecting against animal health risks may in fact be complements, and that the model's production choices come as a complementary package. We then extend the model to endogenize the choice of animal genetics. A finding is that innovations in general infrastructure encourage herd owners to choose more feed efficient, but less hardy, animals. Higher feed conversion efficiency then induces the use of denser feed rations, accelerated finishing and greater levels of biosecurity actions at farm perimeters. Our theory provides a coherent framework for explaining associations among inputs and outcomes that are linked with confined animal agriculture. It also explains how animal protein supply chain technology adoption and performance can differ according to a region's state of infrastructure, why responses to a change in infrastructure may be large, and why public sector efforts to reduce production risk may beget private sector effort to do so.